Modelo de pronóstico para la producción de sal - Amoroso Rodríguez, Lázaro (2018)
This article evaluates gross salt production as a function of evaporation and precipitation, as variables, using simple and quadratic linear regression statistical analysis. Crude salt production and meteorological variables records belonging to 35 years, are used for a case study in Caimanera, Guantanamo Bay, Cuba. The (r) coefficient of correlation is used for a regression model. The results of different statistical models are shown and compared, and information generated from these results is discussed as the basis for a mathematical forecasting model that allows decision making to optimize production.